Multivariate six sigma: A key improvement strategy in industry 4.0. Issue Volume 33:Issues 4(2021) (2nd October 2021) - Ferrer, Alberto
Abstract: This article aims to generate a reflection on the changes that need to be made in the Six Sigma strategy so that it continues to be a successful improvement strategy capable of facing the new challenges derived from Industry 4.0.